Corporate Social Responsibility in Timika Papua - Muh. Jihad Firman; Fahkri Kahar; Andi Caesar To Taddampali (Universitas Negeri Makassar, 2020)
Corporate Social Responsibility (CSR) is an investment for companies for the company's growth and sustainability (sustainability) and is no longer seen from the cost center but as a profit center. The purpose of this study was to determine the Corporate Social Responsibility (CSR) in Timika Papua. This study uses a quantitative approach. Research data sources are primary data and secondary data. Data collection techniques used were documentation, questionnaire and observation. The population and research sample used were 100 respondents. Analysis of the data used is by using multiple linear analysis. The results showed that Corporate Social Responsibility in the fields of education, health and social capital had a positive and significant effect on Timika Papua. In the field of education PTFI provides assistance such as scholarships, construction of educational facilities and infrastructure, teacher assistance and education campaigns. In the health sector PTFI provides health services for the community and conducts community health programs. In the field of social capital, PTFI conducts infrastructure development and provides facilities for places of worship.